FOR PHARMACEUTICAL COMPANIES LISTED ON BEI, FINANCIAL COMPANY ANALYSIS USING Z-SCORE AND LOGIT METHOD - Ari Nurcahyo Darmawan, (JOURNAL KOPERASI DAN MANAJEMEN, 2022)
Purpose – This research aimed to determine the pharmaceutical company’s financial condition listed on JSX between 2015 and 2019 using the Altman Model (Z-Score) and the Zavgren Model (Logit) and whether there was a significant difference between the results of the company’s financial condition valuation using both models. Design/methodology/approach – The type of research that was conducted as a case study. The company's data was obtained from the Jakarta Stock Exchange. The data analysis techniques used were the Altman Model (Z-Score), the Zavgren Model (Logit), and Chi-Square analysis. Findings – The study's findings revealed that, first, the company's financial condition based on the Altman Model (Z-Score) in 2015 (4 healthy and 7 critical), 2016 (5 healthy and 4 critical), 2017 (4 healthy, 1 critical, and 1 potentially bankrupt), 2018 (6 healthy, 2 critical, and 1 potentially bankrupt), and 2019 (6 healthy, 2 critical, and 1 potentially bankrupt) (4 healthy and 5 critical). Second, the company's financial condition in 2015 (2 healthy, 6 critical, and 2 potentially bankrupt), 2016 (2 healthy, 2 critical, and 2 potentially bankrupt), 2017 (2 healthy, 6 critical, and 1 potentially bankrupt), 2018 (3 healthy, 4 critical, and 2 potentially bankrupt), and 2019 (3 healthy, 4 critical, and 2 potentially bankrupt). Research limitations/implications – Only pharmaceutical businesses registered on the JSE are included in the calculation of the interval range to establish the cut-off point in the Zavgren model (logit) analysis. If pharmaceutical businesses that are not listed on the JSE are also included in the calculation, the results of the interval range calculation will be more accurate. Originality/value – To improve its financial position or boost its Z-score, the company should optimize the use of all current assets to enhance sales, which is predicted to increase company profits. Keywords : Financial analysis, Z-Score, Logit, Altman, Zavgren Paper type: Case Study